PENGARUH KOMPETENSI, INDEPENDENSI, KONFLIK PERAN, KETIDAKJELASAN PERAN TERHADAP KINERJA AUDITOR DENGAN KECERDASAN EMOSIONAL SEBAGAI VARIABEL MODERASI (Studi Empiris pada KAP di DKI Jakarta) (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to determine the influence of competence, independence,role conflict, role ambiguity on auditor performance with emotional quotient as amoderating variable at public accountant firms in The Special Capital Region ofJakarta. The population of this research is 274 public accountant firms. Further,the sample method used was purposive sampling technique that obtained specificsample criterion which was only 54 internationally affiliated public accountantfirms selected for this study. The data gathered in this study is the primary datawhich were collected through questioners. As much as 162 questioners spread tothe participants, there were only 90 questioners returned completely. The dataanalysis technique in this study is multiple linear regression and moderateregression analysis method using SPSS 23 statistics software. The result of thestudy proved that there is a significant influence among competence,independence, role conflict, role ambiguity on auditor performance. Emotionalquotient can be a moderating variable to competence, independence, role conflict,role ambiguity.Keywords : competence, independence, role conflict, role ambiguity, emotionalquotient, auditor performance